Break the wheel : ending the cycle of police violence - Ellison, Keith, 1963- (Twelve, 2023)
"BREAK THE WHEEL takes the reader through different solutions that will make way for a defining, generational moment of racial reckoning and social justice understanding. The murder of George Floyd sparked global outrage. At the center of the conflict, the controversy and the trial, Keith Ellison grappled with how to bring justice for Floyd and his family, and now, in the pages of this important book, aims to find the best approaches to put an end to police brutality once and for all. Each chapter of BREAK THE WHEEL works through a different spoke of the tragedy and its causes. The first chapter channels George Floyd's perspective as Ellison narrates the high stakes tension of the trial. The next chapter comes at the issue from a cop's viewpoint as Ellison sits down with white and BIPOC officers to discuss police reform. From there this book goes spoke to spoke on the wheel with Ellison in conversation with prosecutors, heads of police unions, historians (to capture the troubled history of policing), judges, activists, legislators, politicians, and media figures, in attempt to end this chain of violence and replace it with empathy and shared insight. While it may seem like an unattainable goal, BREAK THE WHEEL demonstrates through Ellison's analysis of George Floyd's life, alongside rich historical context, that lasting change can be achieved with informed solutions"--